2013
DOI: 10.1371/journal.pone.0068957
|View full text |Cite
|
Sign up to set email alerts
|

Buried in Sands: Environmental Analysis at the Archaeological Site of Xiaohe Cemetery, Xinjiang, China

Abstract: Palynomorphs extracted from the mud coffins and plant remains preserved at the archaeological site of Xiaohe Cemetery (Cal. 3980 to 3540 years BP) in Lop Nur Desert of Xinjiang, China were investigated for the reconstruction of the ancient environments at the site. The results demonstrate that the Xiaohe People lived at a well-developed oasis, which was surrounded by extensive desert. The vegetation in the oasis consisted of Populus , Phragmites , Typha and probably of Gramineae, while the desert surround… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…In our opinion, it is consistent with pollen grains of Ephedra, several species of which are endemic to Iran [14]. All of these features are typical of the pollen from the genus Ephedra [15,16] (Fig. 3).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…In our opinion, it is consistent with pollen grains of Ephedra, several species of which are endemic to Iran [14]. All of these features are typical of the pollen from the genus Ephedra [15,16] (Fig. 3).…”
supporting
confidence: 84%
“…In arid regions, analyses of archaeological sites proves that pollen and macrofossils Ephedra can be encountered [16][17][18][19][20][21][22][23][24][25] (Fig. 4).…”
mentioning
confidence: 99%
“…Trace element and pollen analysis found that between 4000 and 3450 years BP, the climate was relatively moist, and that the Lop Nor reached a peak water level (Xia et al 2008;Shu et al 2003). In addition, pollen and phytolith analysis at the Xiaohe Cemetery also discovered that the water level of the Xiaohe River (a branch of the Peacock River) was sufficient and flowing during this period (Li et al 2013;Qiu et al 2014). In the Tarim Basin, glacial meltwater fed a number of inland rivers and streams, which supported a large number of oases around the margins of the basin and along the banks of their watercourses (Tang et al 2013).…”
Section: Palaeoenvironmental Implicationsmentioning
confidence: 97%
“…The desiccating effects of warm dry environment have been known for millennia: in their burial practices, the Tocharian peoples of the Xingjian Autonomous region in Western China desiccated and mummified the bodies of their dead in the hyper-arid climate of the Tarim desert basin [32]. In analogy, warm dry CO 2 insufflation causes desiccation and crenation of the peritoneal mesothelium.…”
Section: Warm Dry Co 2 Insufflationmentioning
confidence: 99%